Salvianolic acid A reverses cisplatin resistance in lung cancer A549 cells by targeting c-met and attenuating Akt/mTOR pathway - Xia-li Tang; Li Yan; Ling Zhu; De-min Jiao; Jun Chen; Qing-yong Chen (Elsevier, 2017)
Drug resistance is one of the leading causes of chemotherapy failure in non-small cell lung cancer (NSCLC) treatment. The purpose of this study was to investigate the role of c-met in human lung cancer cisplatin resistance cell line (A549/DDP) and the reversal mechanism of salvianolic acid A (SAA), a phenolic active compound extracted from Salvia miltiorrhiza. In this study, we found that A549/DDP cells exert up-regulation of c-met by activating the Akt/mTOR signaling pathway. We also show that SAA could increase the chemotherapeutic efficacy of cisplatin, suggesting a synergistic effect of SAA and cisplatin. Moreover, we revealed that SAA enhanced sensitivity to cisplatin in A549/DDP cells mainly through suppression of the c-met/AKT/mTOR signaling pathway. Knockdown of c-met revealed similar effects as that of SAA in A549/DDP cells. In addition, SAA effectively prevented multidrug resistance associated protein1 (MDR1) up-regulation in A549/DDP cells. Taken together, our results indicated that SAA suppressed c-met expression and enhanced the sensitivity of lung adenocarcinoma A549 cells to cisplatin through AKT/mTOR signaling pathway.